Investigating stress, anxiety, social support and sex satisfaction on physical education and sports teachers during the COVID-19 pandemic. Issue 8 (August 2021) - Ali, Mohammed Feroz; Kundra, Sakul; Alam, Mohammad Afsar; Alam, Mumtaz
Abstract: Academia was no exception to the widespread impact of Coronavirus Disease (COVID-19). There is only a small amount of research conducted with regard to the consequences of the Pandemic in Fiji. Thus, in order to gather a longitudinal dataset, a cross-sectional survey was conducted from February to August 2020. 300 physical education and sports teachers used Google Forms to complete an online survey. There are questions on the form about age, gender, marital status, and other daily activities. A similar survey was conducted to study the long-term psychological effects (coronavirus fear and fascination with COVID-19). The characteristics of society have been explored. Efforts have been made to use different sets of psychological data, showing the anticipated results. Sex, age, marital status, and family type are significantly affected by stress, anxiety, sexual satisfaction, and social support. There is a substantial difference between marital status, gender, and social support when it comes to the Pandemic. According to research findings, fifty per cent of secondary school physical education and sports teachers in Fiji may have been affected by the Pandemic. Considerations should be taken to keep teachers calm during a pandemic. Because of this, it is necessary to submit some practical recommendations in order to minimize the adverse effects of this problem. Abstract : COVID-19; Pandemic; Physical education; Psychological; Sports teachers; Fiji